The importance of hygiene in online space - Illia Maksymchuk; Larysa Tereminko; Теремінко Лариса (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. In the modern world, where education and communication increasingly depend on digital technologies, proper digital hygiene is a fundamental aspect of both personal and institutional security. Every time a person interacts with online resources – by visiting a website, downloading a file, or submitting a form – they face potential cyber threats. For instance, a seemingly harmless link may redirect to a malicious web page containing infected files or to a phishing page designed to steal login credentials. This is just one of many dangers present in the contemporary information environment. In educational settings, where teachers and students constantly exchange data and access shared resources, the risk of digital exposure is significantly higher. The online environment is rife with threats that affect both individuals and institutions engaged in educational activities. Understanding the nature of these threats is the first and most fundamental step toward creating a secure digital learning environment. Phishing is among the most widespread and practical methods used by cybercriminals. It involves sending deceptive messages – often emails that appear to come from legitimate sources such as a school administration, a teacher, or popular services like Google Drive or Microsoft 365. The recipient may be asked to verify their account, reset a password, or open a shared document. However, the link provided leads to a fraudulent website designed to capture sensitive information, such as usernames, passwords, and more. Once an attacker gains access to this data, they can infiltrate private systems, send harmful emails from compromised accounts, or even breach an entire institutional network. Phishing remains effective precisely because it targets human behavior rather than technical vulnerabilities.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: digital hygiene; online safety; information environment